Investigation of factors affecting power density radiation of mobile phones - B. Oluwafemi, Ilesanmi; O. Adeoye, Johnson; M. Faluru, Deji; D. Obasanya, Dorcas (International Journal of Engineering and Technology, 2020)
The use of mobile phones in Nigeria has greatly increased in the recent year. This has also increased the general population exposure to mobile phone radiation. In this research, the intensity of radiation around selected mobile phones base on some factors are investigated using Radiofrequency Meter (RF) TM-96, 9V DC and Spectrum Analyzer (NA-773, 144/430 MHz) in a bid to confirm how they affect the radiation level. Measurements were taken at distances of 5 cm from the mobile phones when seeking for connections, calls establishing and calls connections under different conditions such as periods of the day, when charging and when not charging, battery charged levels, single and dual SIMs and network signal levels. The radiation levels from the 5 selected mobile phones ranges from 0.3204 to 0.4824 mW/cm2 during call conversation, with the highest radiating mobile phone being Asus while the least was Infinix 3. The radiation levels of these mobile phones are above the International Commission on Non-ionizing Radiation Protection (ICNIRP) reference level, 0.45 mW/cm2. Results also shows that the cell phone battery level, network signal level, the number of inserted SIM cards increases the radiation level of the mobile phones.Â Â